2015
DOI: 10.1515/secm-2014-0352
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength of Z-pinned laminates in RTD and hot-wet environment

Abstract: Experiments and simulation analysis for tensile strength of Z-pinned laminates were conducted in both room temperature and dry and hot-wet environments. The results of the experiments show that the fracture of [0]6 specimen with Z-pins was longitudinally torn, and there was a row of Z-pins at the fracture of [(±45)/(0,90)]2S specimen with Z-pins. It could be observed that the hot-wet effect on the tensile strength of the Z-pinned laminates increased with percentage of 0-direction fibers decreasing in the lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Numerous studies [25][26][27][28][29] have shown that when the specimen is loaded, there are two types of failure for Z-pins: pull-off failure and shear failure. To investigate the interfacial bonding force between the Z-pin and the matrix of composite material, as well as the toughening mechanism of the Z-pin, the single Z-pin pull-off and shearing processes should be investigated to provide data for simulations.…”
Section: Specimens Manufacture and Testingmentioning
confidence: 99%
“…Numerous studies [25][26][27][28][29] have shown that when the specimen is loaded, there are two types of failure for Z-pins: pull-off failure and shear failure. To investigate the interfacial bonding force between the Z-pin and the matrix of composite material, as well as the toughening mechanism of the Z-pin, the single Z-pin pull-off and shearing processes should be investigated to provide data for simulations.…”
Section: Specimens Manufacture and Testingmentioning
confidence: 99%